ANALISIS KUALITAS PELAYANAN PUBLIK DALAM MODEL SERVQUAL DI PUSKESMAS DUKUN KABUPATEN MAGELANG: PERSPREKTIF MASYARAKAT - habib tutik; Nur Faidati S.IP.,MA (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
This study aims to analyze the quality of public services as the Dukun Community Health Center in Magelang Regency using the SERVQUAL model as an evaluative approach to health service performance. The focus of the study is directed at measuring the gap between community expectations and perceptions of the five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy, and their implications for strengthening local public service governance.The study uses a quantitative descriptive approach with a Likert scale questionnaire instrument (1-4). The sample was determined by the Slovin formula (n=100, e=5%).The analysis was carried out by combining the Community Satisfaction Index (IKM) method and SERVQUAL gap analysis referring to the Regulation of the Minister of Administrative and Bureaucratic Reform No. 14/2017. The results of the study indicate that all dimensions of service quality at the Dukun Health Center are still in the “Poor” category, with the largest gaps in the aspects of infrastructure, limited medical personnel, service waiting times, and low empathy and responsiveness of officers.These findings indentify the need for reformulation of service management strategies based on increasing resource capacity, as well empathetic communication training for health workers.Conceptually, this study contributes to expanding the application of the SERVQUAL model in rural areas and provides an empirical basis for improving community satisfaction-oriented health center governance.